General English Learners’ Perceptions of English for Science and Technology: The Case of Third Year Applied Language Studies Learners, University of Constantine - DJARBOU, Nesrine (Journal of Human Sciences, 2016)
The aim of this article is to investigate third year General English learners’ perceptions of English for Science and Technology. The latter is a subject introduced in the curriculum of “Licence LMD in English” to give students an idea about the basic theoretical notions of EST and to train them for reading, understanding, and writing an EST paragraph. In the Department of English, at the University of Constantine 1, a team of teachers have chosen as a teaching material a textbook which is entitled“Minimum Competence in Scientific English” to teach EST without having carried out a formal evaluation of this textbook to establish its efficacy and suitability to the intended population. This makes it even more interesting to study General English learners’ perceptions towards EST as the content of the textbook presupposes having background knowledge in science and technology and this can be challenging to our learners what intrigues us to know their attitudes. To carry out a thorough evaluation of this coursebook, a questionnaire is given to eighty students chosen randomly from third year linguistics and Applied Language Studies option. The results reveal that the participants are not aware of their needs though they have positive attitudes towards EST.